Study on the changes of blood glucose in hemodialysis patients with diabetes - Lai,Lanshuhui (2021)
SUMMARY OBJECTIVE: The aims of this study were to observe the regularity of blood glucose changes in hemodialysis patients with diabetes, time of onset of hypoglycemia and blood glucose level during dialysis, and to explore the sensitive early warning indicators of hypoglycemia in dialysis patients. BACKGROUND: Diabetes patients have a high incidence of hypoglycemia during hemodialysis. METHODS: A total of 124 maintenance hemodialysis patients with diabetes were selected for this study. Before dialysis, one, two, and three h after dialysis, and when hypoglycemia symptoms occurred, the blood glucose changes were monitored, the blood glucose drop range was observed when hypoglycemia symptoms occurred, and the correlation between the two was analyzed. RESULTS: After the start of the dialysis, the patient’s blood glucose showed a downward trend. The symptoms of hypoglycemia were most obvious within one-two hours, with an incidence rate of 57.9%. When the blood glucose drop percentage reached 37.7%, the specificity and sensitivity of early warning hypoglycemia symptoms were 84.6 and 73%, respectively. CONCLUSIONS: For hemodialysis patients with diabetes, attention should be paid to the symptoms of hypoglycemia during dialysis, and blood glucose should be monitored before dialysis and after 1-2 h of dialysis. If the blood glucose drop percentage is greater than 37.7%, the timely measures should be taken.